WIDOWHOOD AND MORTALITY RISK OF OLDER PEOPLE IN RURAL CHINA: DO GENDER AND LIVING ARRANGEMENT MAKE A DIFFERENCE?. (11th November 2018) - Liu, H; Jiang, Q; Feldman, M
Abstract: Objectives: Increased mortality after spousal bereavement has been observed in many populations. Few studies have investigated the widowhood effect in a traditional culture where the economy is underdeveloped. In this study, we assessed whether the widowhood-associated excess mortality exists and differs by gender and living arrangement in rural China. Methods: The data used in this longitudinal study come from the survey "Well-being of Elderly Survey in Anhui Province (WESAP)", which was conducted every three years between 2001 and 2015 in rural townships of Anhui province. Excluding cases with missing values and restricting the sample to respondents who were married or widowed with adult children at baseline and in follow-up, analyses were carried out on 2, 471 adults aged 60 and above. Cox regression was applied to examine the effects. Results: Spousal loss decreased mortality for older rural Chinese and there was a gender difference in this effect. Analyses also show that living with adult children after spousal loss played a protective role in reducing the risk of older men's death, though it tended to increase older men's mortality risk in general. Conclusion: Our findings suggest that the widowhood effect is culture-specific and spousal loss reduces rather than increases the mortality risk of rural elders in China, which implies that caring for an ill spouse is still a big burden in current rural China though family-based assistance acts as functional solidarity for older people, especially for widowers.